Cranioplasty: An institutional experience - Junior, Aderaldo Costa Alves [UNESP]; Filho, Pedro Tadao Hamamoto [UNESP]; Gonçalves, Marcelo Pacheco [UNESP]; Neto, Aristides Augusto Palhares [UNESP]; Zanini, Marco Antonio [UNESP] (Wolters Kluwer, 2018)
Cranioplasty is a common procedure in neurosurgical practice, but associated with high complication rates. In the current study, the authors describe surgical characteristics and results of cranioplasty performed in a tertiary teaching hospital in Brazil. Data were obtained from electronic medical records of cranioplasties performed between January 2013 and November 2016. The sample comprised of 33 patients, and the mean follow-up time was 16 months. Patients presented most of the times a good preoperative status, with 84.8% of patients classified between 0 and 3 at modified Rankin scale and 78.7% with 4 or 5 points at GlasgowOutcome Scale. The most common initial diagnosis was vascular disease (48% of patients) followed by traumatic brain injury (36% of patients). The majority of cranioplasties used an autograft: the autologous bone flap removed during a previous surgery (craniectomy) and stored in the abdominal subcutaneous fat (67% of patients). In 3 patients, the polymethylmethacrylate prosthesis was custom-made prior to the operation using 3-dimensional printing, based on computed tomography images. Five patients (15% of patients) developed symptoms related to surgical site infection, manifesting at an average of 5 weeks following the procedure. Three of them presented scalp dehiscence before the infection symptoms. Cranioplasty should be performed early, as long as clinical conditions are good and the patient has overcome the acute phase of neurological injury.
Keywords: Neurosurgery; Skull; Traumatic brain injury